A novel type I cystatin of parasite origin with atypical legumain-binding domain - Ilgová, Jana; Jedličková, Lucie; Dvořáková, Hana; Benovics, Michal; Mikeš, Libor; Janda, Lubomír; Vorel, Jiří; Roudnický, Pavel; Potěšil, David; Zdráhal, Zbyněk; Gelnar, Milan; Kašný, Martin (Scientific reports, 2017)
Parasite inhibitors of cysteine peptidases are known to influence a vast range of processes linked to a degradation of either the parasites' own proteins or proteins native to their hosts. We characterise a novel type I cystatin (stefin) found in a sanguinivorous fish parasite Eudiplozoon nipponicum (Platyhelminthes: Monogenea). We have identified a transcript of its coding gene in the transcriptome of adult worms. Its amino acid sequence is similar to other stefins except for containing a legumain-binding domain, which is in this type of cystatins rather unusual. As expected, the recombinant form of E. nipponicum stefin (rEnStef) produced in Escherichia coli inhibits clan CA peptidases - cathepsins L and B of the worm - via the standard papain-binding domain. It also blocks haemoglobinolysis by cysteine peptidases in the worm's excretory-secretory products and soluble extracts. Furthermore, we had confirmed its ability to inhibit clan CD asparaginyl endopeptidase (legumain). The presence of a native EnStef in the excretory-secretory products of adult worms, detected by mass spectrometry, suggests that this protein has an important biological function at the host-parasite interface. We discuss the inhibitor's possible role in the regulation of blood digestion, modulation of antigen presentation, and in the regeneration of host tissues.
Keywords: Animals; ploštěnci; Sequence Analysis, Protein; Helminth Proteins; Escherichia coli; počítačová simulace; kapři; vazba proteinů; proteinové domény; rekombinantní proteiny; Recombinant Proteins; Cystatins; Protein Domains; Computer Simulation; Phylogeny; Protein Conformation; cysteinové endopeptidasy; Cloning, Molecular; Cysteine Endopeptidases; Sequence Alignment; Carps; konformace proteinů; Platyhelminths; klonování DNA; proteiny červů; zvířata; fylogeneze; sekvenční analýza proteinů; cystatiny; Protein Binding; sekvenční seřazení